Shadaqah Obligah as a Reconstruction of the Settlement of Inheritance Disputes Between Daughters and Brothers of the Heirs in the Perspective of Islamic Inheritance Law in Indonesia - FERY DINANTA GINTING (Program Pascasarjana UIN Sumatera Utara Medan, 2026)
Disputes over the distribution of inheritance between daughters and heiress brothers are still one of the issues that often cause conflict in the practice of Islamic inheritance law in Indonesia. The difference in views between classical jurisprudence, the Compilation of Islamic Law (KHI), and the jurisprudence of the Supreme Court has led to the lack of uniformity in the settlement of the case. On the one hand, Sunni jurisprudence gives the right to a brother as an 'ashabah when the heir only leaves a daughter, while on the other hand, the development of Supreme Court jurisprudence places girls as heirs who can hijab the heir's brother. These differences not only cause legal uncertainty, but also trigger disharmony in family relationships. This study aims to analyze the development of regulations regarding the position of girls to male heirs in Islamic inheritance law in Indonesia and offers a settlement model that is more oriented towards substantive justice and family benefits. The research uses normative legal research methods with a statutory approach, a conceptual approach, and a case approach through an analysis of the Compilation of Islamic Law, Supreme Court decisions, classical jurisprudence literature, and contemporary Islamic legal doctrines. The data was analyzed qualitatively using the theory of maslahah and maqāṣid al-syarī'ah as the analysis knife. The results of the study show that both the classical fiqh approach and the Supreme Court's jurisprudence approach have not been fully able to resolve the social conflicts that arise in the practice of inheritance distribution. Therefore, this study offers a reconstruction of dispute resolution through the concept of obligatory shadaqah, which is the giving of part of the property to the heir's brother not as an inheritance right, but as a form of giving based on the principles of benefit, propriety, and family sincerity. The model is able to maintain a balance between legal certainty, substantive justice, and harmony of family relations without changing the normative provisions regarding inheritance that have been established in Islamic law.